2022
DOI: 10.3389/fpubh.2022.949062
|View full text |Cite
|
Sign up to set email alerts
|

The impact of media use on disparities in physical and mental health among the older people: An empirical analysis from China

Abstract: BackgroundThe media is playing an increasingly important role in the lives of older adults. Exploring health inequalities in older adults is essential for achieving healthy aging. However, few studies have focused on the effects of different media types on older adults' physical and mental health levels and health inequalities among older adults with varying levels of education from a health communication perspective.ObjectivesThe purpose of this study was to investigate the media use, physical and mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Despite the rapid advances in internet technology and its widespread use in recent decades, internet usage among the elderly remains low, particularly in developing countries [ 2 ]. Recently, evidence has indicated that older internet users are less likely to experience mental health issues such as loneliness and physical disorders like functional limitations [ 2 4 ]. Internet use can also facilitate access to health information for the elderly, thus improving their health literacy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the rapid advances in internet technology and its widespread use in recent decades, internet usage among the elderly remains low, particularly in developing countries [ 2 ]. Recently, evidence has indicated that older internet users are less likely to experience mental health issues such as loneliness and physical disorders like functional limitations [ 2 4 ]. Internet use can also facilitate access to health information for the elderly, thus improving their health literacy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The built environment’s impact on health is found to be moderated and mediated by PM 2.5 levels and housing prices, offering crucial insights for mitigating health inequalities through informed urban planning in China. 79 In Africa as well, similar trends are seen—A study addressed the lack of long-term air pollution exposure data in growing sub-Saharan African cities by developing high-resolution spatiotemporal land use regression models to map PM 2.5 and black carbon concentrations in the Greater Accra Metropolitan Area. The 1-year measurement campaign at 146 sites informed the models, revealing that 48% to 69% and 63% to 71% of the variance in PM 2.5 and black carbon concentrations, respectively, could be explained by factors related to road traffic, vegetation, and temporal variables.…”
Section: The Complex Interaction Of Different Environments In the Exp...mentioning
confidence: 88%
“…First, limited by the secondary data analysis, we failed to assess and control variables that might influence the inference of our study. For example, older adults are accustomed to using traditional media [ 44 ], which may also transfer PA-related information and influence the outcome of interest in this study. Additionally, the built environment is particularly relevant to the PA of older adults [ 45 , 46 ], and this variable was not included in PAHIOWS either.…”
Section: Discussionmentioning
confidence: 99%